A survey of current United Kingdom practice for antenatal screening for inherited disorders of globin chain synthesis. UK Forum for Haemoglobin Disorders. Issue 5 (May 1998) - Bain, B J; Chapman, C
Abstract : AIMS: To document current United Kingdom practice for antenatal screening for inherited disorders of globin chain synthesis and to compare such practice with guidelines published by the British Committee for Standards in Haematology and the Standing Committee on Sickle Cell, Thalassaemia and other Haemoglobinopathies (SMAC). METHODS: The members of the UK Forum on Haemoglobin Disorders were surveyed about their current practice for antenatal haemoglobinopathy screening. The UK Forum is a national group of haematologists, paediatricians, laboratory scientists, and counsellors working in the field of diagnosis and management of disorders of haemoglobin synthesis; such disorders including the alpha and beta thalassaemias, sickle cell disease, and other haemoglobinopathies. RESULTS: Completed questionnaires from 38 hospitals (or cooperating groups of hospitals) were analysed. The great majority of hospitals were applying appropriate laboratory methods, but problems were commonly encountered in ensuring that appropriate testing of antenatal patients and, when necessary, of their partners, was carried out early in pregnancy. When screening was selective there was quite often a failure to identify all women in whom testing was indicated, and cut off points used as an indication for further testing were sometimes inappropriate. CONCLUSIONS: Many practical problems are still encountered in following guidelines for the antenatal diagnosis of haemoglobinopathies. A need for improved administrative procedures and increased funding was identified. In addition there is a need for agreed guidelines giving more specific advice on technical aspects of laboratory practice.